PSVII-27 Impact of manure storage system on odor, carbon dioxide, and methane from swine manure. (7th December 2018) - Hwang, O; Trabue, S; Andersen, D; Scoggin, K
Abstract: Swine manure stored in deep-pits are a major source of odor from livestock building and a significant air pollutant that potentially impacts both animals and farm employees. Flushing systems dilute manure using water or lagoon effluent to flush manure and reduce odor. In this study, the effect of swine manure dilution on odor, carbon dioxide (CO2), and methane (CH4) were compared. Manures from two finishing deep-pit representing early (two week) and late (one year) were combined with lagoon effluent in bioreactors. Reactors were loaded initially with either manure (control) or lagoon effluent and, manure was added daily to each bioreactor at 5% of final volume. Final manure to lagoon ratios was 10:0 (control), 7:3, 5:5, and 2:8. At the end of each treatment, headspace gas was sampled for volatile fatty acids, phenols, and indoles using sorbent tubes with GC/MS analysis and ammonia, CO2, and CH4 were measured with photoacoustic infrared instrument. Bioreactor contents were analyzed for odorant concentrations, total solids, and pH. Headspace odor was dominated by phenols and straight chain fatty acids. Odor decreased on average 1.7% for each percent dilution of manure. Based on the solids content, odor increased on average 9.9% for each percent increase in manure solids. However, CO2 and CH4 had a different pattern since concentrations increased on average by 25.0% and 32.8% compared to control. There were increased foam with manure dilution and pH with time. In this study, factors that contribute to decrease of in odor, CO2, and CH4 include: 1) solids content, 2) manure pH and 3) enhanced foam production.